Peran Guru Dalam Meningkatkan Kemampuan Anak Memecahkan Masalah Di Sentra Bahan Alam Kelompok A - Tiara; Sri Wahyuningsi Laiya; Nunung S. Jamin; Sari, Mita (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
It applied a qualitative approach with a descriptive method and employed data collection techniques such as observation, interviews, and documentation. The study's subjects were the teachers and children at the research site. The data analysis involved describing the relevant findings obtained in the field regarding the aforesaid problem. The research findings indicated that teachers play a crucial role in the process of developing problem-solving skills in the context of the Natural Materials Center. Teachers need to employ engaging and experimental teaching methods that align with children's interests to fulfill this role. In conclusion, the teachers have successfully enhanced children's problem-solving abilities by acting as facilitators/informants, mediators, and classroom managers